Discovery and process development of a novel TACE inhibitor for the topical treatment of psoriasis. Issue 4 (15th February 2018) - Boiteau, Jean-Guy; Ouvry, Gilles; Arlabosse, Jean-Marie; Astri, Stéphanie; Beillard, Audrey; Bhurruth-Alcor, Yushma; Bonnary, Laetitia; Bouix-Peter, Claire; Bouquet, Karine; Bourotte, Marilyne; Cardinaud, Isabelle; Comino, Catherine; et al.
Graphical abstract: Abstract: Targeting the TNFα pathway is a validated approach to the treatment of psoriasis. In this pathway, TACE stands out as a druggable target and has been the focus of in-house research programs. In this article, we present the discovery of clinical candidate26a . Starting from hits plagued with poor solubility or genotoxicity, 26a was identified through thorough multiparameter optimisation. Showing robust in vivo activity in an oxazolone-mediated inflammation model, the compound was selected for development. Following a polymorph screen, the hydrochloride salt was selected and the synthesis was efficiently developed to yield the API in 47% overall yield.